Technology and Reading Performance in the Middle-School Grades: A Meta-Analysis with Recommendations for Policy and Practice1 - Juan Moran; Richard E. Ferdig; P. David Pearson; James Wardrop; Robert L. Blomeyer, Jr. (2008)

Technology and reading performance in the middle-school grades: A meta-analysis with recommendations for policy and practice - Juan Moran; Richard E. Ferdig; P. David Pearson; James Wardrop; Robert L. Blomeyer, Jr. (Journal of Literacy Research, 2008)
The results of a meta-analysis of 20 research articles containing 89 effect sizes related to the use of digital tools and learning environments to enhance literacy acquisition for middle school students demonstrate that technology can have a positive effect on reading comprehension (weighted effect size of 0.489). Very little research has focused on the effect of technology on other important aspects of reading, such as metacognitive, affective, and dispositional outcomes. The evidence permits the conclusion that there is reason to be optimistic about using technology in middle-school literacy programs, but there is even greater reason to encourage the research community to redouble its efforts to investigate and understand the impact of digital learning environments on students in this age range and to broaden the scope of the interventions and outcomes studied.
Keywords: cognition; compréhension; contexte d'apprentissage; école secondaire; lecture numérique; pratiques pédagogiques